2018
DOI: 10.2131/jts.43.611
|View full text |Cite
|
Sign up to set email alerts
|

Differential impacts of mineralocorticoid receptor antagonist potassium canrenoate on liver and renal changes in high fat diet-mediated early hepatocarcinogenesis model rats

Abstract: Mineralocorticoid receptor (MR)/NADPH oxidase (NOX) signaling is involved in the development of obesity, insulin resistance, and renal diseases; however, the role of this signaling on steatotic preneoplastic liver lesions is not fully elucidated. We determined the effects of the MR antagonist potassium canrenoate (PC) on MR/NOX signaling in hepatic steatosis and preneoplastic glutathione S-transferase placental form (GST-P)-positive liver foci. Rats were subjected to a two-stage hepatocarcinogenesis model and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Effects of the HFD on GST-P-positive preneoplastic liver foci were variable in our studies, probably reflecting variations due to the study condition and diet lot. Both the area and number of foci were significantly increased in the HDF group compared with the CTL group in our previous study (Murayama et al, 2018) or were both weakly increased without a significant difference in another study (Nakamura et al, 2018). The present study revealed only a minor effect on the number of GST-P-positive preneoplastic liver foci.…”
Section: Discussionsupporting
confidence: 45%
See 4 more Smart Citations
“…Effects of the HFD on GST-P-positive preneoplastic liver foci were variable in our studies, probably reflecting variations due to the study condition and diet lot. Both the area and number of foci were significantly increased in the HDF group compared with the CTL group in our previous study (Murayama et al, 2018) or were both weakly increased without a significant difference in another study (Nakamura et al, 2018). The present study revealed only a minor effect on the number of GST-P-positive preneoplastic liver foci.…”
Section: Discussionsupporting
confidence: 45%
“…To elucidate the effects of the HFD feeding, we initially examined the histopathology of liver tissue using the NAS scoring system (Kleiner et al, 2005) with gene expression analysis for lipid metabolism and oxidative stress. NAS is suitable to evaluate NAFLD and NASH in the liver obtained from patients and rodent models (Itagaki et al, 2013;Nakamura et al, 2018). The HFD increased NAS with ballooning changes in the liver sections, although there was no significant change in steatosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations